Acceptability of the POWERPLAY Program: A Workplace Health Promotion Intervention for Men. (November 2017) - Seaton, Cherisse L.; Bottorff, Joan L.; Oliffe, John L.; Jones-Bricker, Margaret; Caperchione, Cristina M.; Johnson, Steven T.; Sharp, Paul
The workplace health promotion program, POWERPLAY, was developed, implemented, and comprehensively evaluated among men working in four male-dominated worksites in northern British Columbia, Canada. The purpose of this study was to explore the POWERPLAY program's acceptability and gather recommendations for program refinement. The mixed-method study included end-of-program survey data collected from 103 male POWERPLAY program participants, interviews with workplace leads, and field notes recorded during program implementation. Data analyses involved descriptive statistics for quantitative data and inductive analysis of open-ended questions and qualitative data. Among participants, 70 (69%) reported being satisfied with the program, 51 (51%) perceived the program to be tailored for northern men, 56 (62%) believed the handouts provided useful information, and 75 (74%) would recommend this program to other men. The findings also highlight program implementation experiences with respect to employee engagement, feedback, and recommendations for future delivery. The POWERPLAY program provides an acceptable approach for health promotion that can serve as a model for advancing men's health in other contexts.